Odpowiedzi

2009-11-27T18:25:20+01:00
A) (3xy-5x²y)-(10xy -2x²y) = 3xy-5x²y-10xy +2x²y=-7xy-3x²y
b) (-12abc-4a²bc)-(abc+a²bc)+12 =
= -12abc-4a²bc-abc-a²bc+12= -13abc-5a²bc+12
c) (1⅗x³+⅔ y²-⅚)-(2,4x³+y²-1⅙)=1⅗x³+⅔ y²-⅚-2,4x³-y²+1⅙=
=(8/5)x³ + ⅔ y² -⅚ -(12/5) x³-y²+ 7/6=
=(-4/5)x³- (1/3)y²+1/3
d) (0,5x²y²-⅔ab-1)-(-⅓x²y²+1/12 ab-¼) =0,5x²y²-⅔ab-1+⅓x²y²-1/12 ab+¼=
=3/6x²y²-(8/12)ab-1+(2/6)x²y²-1/12 ab+¼=(5/6)x²y²-(9/12)ab-3/4=(5/6)x²y²-(3/4)ab-3/4
36 4 36
Najlepsza Odpowiedź!
2009-11-27T18:27:47+01:00
A) (3xy-5x²y)-(10xy -2x²y) =3x-5x²y-10xy+2x²y=-7x-3x²y
b) (-12abc-4a²bc)-(abc+a²bc)+12 = -12abc-4a²bc-abc-a²bc+12=11abc-5a²bc+12
c) (1⅗x³+⅔ y²-⅚)-(2,4x³+y²-1⅙)= 1⅗x³+⅔y²-⅚-2,4x³-y²+1⅙=-0,8x³-⅓y²+⅓
d) (0,5x²y²-⅔ab-1)-(-⅓x²y²+jedna dwunasta ab-¼) =
0,5x²y²-⅔ab-1+⅓x²y²-¹/₁₂ab+¼+0,8(3)x²y²-¾ab-¾
65 4 65
2009-11-27T18:35:59+01:00
A) (3xy-5y²y)-(10xy-2x²y)=3xy-5x²y-10xy+2x²y=-7xy-3x²y
b)(-12abc-4a²bc)-(abc+a²bc)+12 =-12abc-4a²bc-abc-a²bc+12=
=-13abc-5a²bc+12
c)(1⅗x³+⅔ y²-⅚)-(2,4x³+y²-1⅙)=1⅗x³+⅔ y²-⅚-2,4x³-y²+1⅙=
=1,6x³+⅔ y²-⅚-2,4x³-y²+1⅙=-0,8x³-⅓ y²+dwie szóste
d)(0,5x²y²-⅔ab-1)-(-⅓x²y²+jedna dwunasta ab-¼) =
=0,5x²y²-⅔ab-1+⅓x²y²-jedna dwunasta ab+¼=
=0,5x²y²- osiem dwunastych ab-1+⅓x²y²-jedna dwunasta ab+¼=
=-dziewięć dwunastych ab +0,83x²y²-1
Mam nadzieje ze Naj....
Pozdro
13 3 13